2020
DOI: 10.1111/geb.13085
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to noise pollution across North American passerines supports the noise filter hypothesis

Abstract: The noise filter hypothesis predicts that species using higher sound frequencies should be more tolerant of noise pollution, because anthropogenic noise is more intense at low frequencies. Recent work analysed continental-scale data on anthropogenic noise across the USA and found that passerine species inhabiting more noise-polluted areas do not have higher peak song frequency but have more complex songs. However, this metric of song complexity is of ambiguous interpretation, because it can indicate either div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Such abilities could predispose to successful colonization of urban settlements, a proposal in line with what was previously postulated for the same species [35]. In fact, song learning and plasticity [74] and larger bandwidths in songs [75] appear to be better pre-adaptations for colonizing cities. The repertoire of the Chiguanco Thrush is composed of a wide diversity of motif and twitter elements, and, considering all possible combinations and improvisations, this situation potentially provides the previous natural ability to produce highly variable inter-and intra-individual songs.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Such abilities could predispose to successful colonization of urban settlements, a proposal in line with what was previously postulated for the same species [35]. In fact, song learning and plasticity [74] and larger bandwidths in songs [75] appear to be better pre-adaptations for colonizing cities. The repertoire of the Chiguanco Thrush is composed of a wide diversity of motif and twitter elements, and, considering all possible combinations and improvisations, this situation potentially provides the previous natural ability to produce highly variable inter-and intra-individual songs.…”
Section: Resultssupporting
confidence: 77%
“…The "noise filter hypothesis" postulates that species that naturally sing at lower frequencies are more sensitive to urban noise, affecting the composition of urban bird communities [8,75,81,82]; but see [83,84]. Therefore, the Chiguanco Thrush could be more pressured in the urban colonization process because extra-urban individuals had a mean minimum frequency around the upper limit of the dominant anthropogenic sound frequencies (2 kHz) [20], and a mean dominant frequency around 650 Hz up.…”
Section: Acoustic Communication Responses To Urbanization Are Likely ...mentioning
confidence: 99%
“…Multispecies studies and meta-analyses have revealed similar patterns of habitat filtering based on acoustic signal characteristics for bird distributions in response to anthropogenic noise (Francis 2015. In these cases, the most prominent pattern is that lowfrequency noise tends to decrease habitat use most strongly among birds with low-frequency vocalizations, a pattern that has been dubbed the noise filter hypothesis (Cardoso et al 2020). More recently, an experimental study that implemented landscape-scale playback of sounds of rushing rivers identified a strong link between the strength and direction of species changes in abundance in response to background sounds and vocal frequency (Gomes et al 2021c).…”
Section: Noise Filtering By Traitsmentioning
confidence: 97%
“…Francis [ 43 ] analysed data from 183 bird species from Europe, North America and the Caribbean and found that species communicating with low frequency vocalizations tended to avoid noisy areas, but species with higher frequency vocalizations responded less aggressively. A similar comparative study shows that North American passerines using a larger frequency bandwidth were more tolerant to noise pollution [ 44 ]. However, this does not mean that species with higher-pitched songs are more likely to be more abundant in areas with noise pollution [ 44 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar comparative study shows that North American passerines using a larger frequency bandwidth were more tolerant to noise pollution [ 44 ]. However, this does not mean that species with higher-pitched songs are more likely to be more abundant in areas with noise pollution [ 44 46 ]. Rather, it suggests that their song will be less vulnerable to noise masking, which may allow them to get the message across a noisy environment without the need to adjust their spectral and temporal song parameters.…”
Section: Introductionmentioning
confidence: 99%